Determinants of tax morale among Nepalese taxpayers: An integrated study of knowledge, attitudes, and institutional credibility - Bidari, Dinesh; Khanal, Vishnu (A Bi-annual South Asian Journal of Research & Innovation, 2026)
The paper is explored on compliance intention with individual taxpayers in Nepal, the role of tax knowledge, taxpayer attitudes, and institutional credibility on the same. Data were gathered on 400 taxpayers in Chitwan, Makwanpur and Lalitpur using a quantitative research study design through a structured questionnaire on a five-point Likert scale. Stratified random sampling allowed the coverage of the key taxpayer groups, and the data were analyzed with the help of descriptive statistics and Spearman correlation. Findings indicate that taxpayers have moderate expertise about digital tax relevant digital tax processes included online PAN registration, IRD web services and digital payment systems, although there is still a gap in awareness regarding deadlines, withholding adjustments, and how to get a refund. Generally positive intentions are also exhibited through compliance behaviour, where many respondents indicate correct filings and submission on time. There was a significantly positive and significant correlation between tax knowledge and the intention to comply voluntarily (r = 0.73, p = 0.003) indicating that more informed taxpayers have significantly high chances of voluntarily complying. The behaviour is also affected by attitudes and institutional credibility with taxpayers who have greater perception of fairness, transparency and administrative reliability being more willing to comply. The researchers find that to raise the level of voluntary tax compliance in Nepal one should work towards better tax literacy, simplification of procedures, support of digital services, as well as increase institutional trust.